The Internalization of Prophetic Values in the Poems “Sang Utusan” and “Musim Panen” by Kuntowijoyo - Mukaromah , Umi Roisatul; Ningrum , Asti Tiana; Rabbani, Ilham; Rizky , Auzia Fadhila; Madona , Prita Teresna; Kusuma , Santi Dwi (Journal Corner of Education, Linguistics, and Literature, 2024)
This study aims to explore the internalization of prophetic values in the poems "Sang Utusan" and "Musim Panen" by Kuntowijoyo. The analysis employs a prophetic literary criticism perspective using a descriptive qualitative method. The prophetic values examined in this research include aspects of humanization, liberation, and transcendence. The results of the study indicate that humanization is reflected in the persona’s loving attitude, simplicity, and concern for the suffering of society or the underprivileged. Meanwhile, liberation is expressed as an appeal to break free from the shackles of materialism, hedonism, and the pursuit of power, in favor of a life with moral and spiritual meaning. Transcendence is revealed through the character's spiritual awareness, which enables them to receive and convey the will of God in a profound manner. Through the use of symbolism in the poems, Kuntowijoyo as the author demonstrates that prophetic values have the potential to reach the deepest dimensions of the reader’s self. Therefore, literary works are not merely expressions of aesthetic experience, but also serve as instruments for promoting social and spiritual transformation.